“ANALISIS KESULITAN BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN JARAK JAUH (PJJ) DI TENGAH PANDEMI COVID-19”. - Milana Abdillah Subarkah; Agus Salim (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2021)
ABSTRACTThe teaching and learning process is a very important activity and must be carried out even though the situation is not possible in schools amid the Covid-19 pandemic as it is today. So this study aims to analyze learning difficulties, distance learning, and analysis of student learning difficulties in PJJ amid the Covid-19 pandemic. This research uses a qualitative approach to the type of case studies, in-depth interviews, and documentation studies. The results of the study show First, learning difficulties in students can be experienced due to disruption in him both from within and outside himself. This condition can also occur amid the Covid-19 pandemic. In the end, through various appeals from several parties, students were asked to carry out their learning activities in their respective homes. Second, with the appeals and suggestions of students studying at home, then Distance Learning (PJJ) becomes an alternative learning activity for students in order to break the corona virus transmission chain. Third, during the Covid-19 pandemic with PJJ students faced problems accessing internet devices and quotas, thus the government and all education administrators to provide internet quota subsidies, emergency curricula, and develop effective learning strategies for communities affected by Covid-19.